From “ghost in the machine” to “spiritual automaton”: Philosophical meditation in Wittgenstein, Cavell, and Levinas - Vries, Hent de (International journal for philosophy of religion, 2006)
This essay discusses Stanley Cavell’s remarkable interpretation of Emmanuel Levinas’s thought against the background of his own ongoing engagement with Wittgenstein, Austin, and the problem of other minds. This unlikely debate, the only extensive discussion of Levinas by Cavell in his long philosophical career sofar, focuses on their different reception of Descartes’s idea of the infinite. The essay proposes to read both thinkers against the background of Wittgenstein’s model of philosophical meditation and raises the question as to whether Cavell and Levinas do not indirectly shed light on the early modern motif of the spiritual automaton.